FACTORS AFFECTING POVERTY IN EAST NUSA TENGGARA PROVINCE IN 2017-2022 - Feniza Dwi Pandina; Barika Barika (SEAN Institute, 2023)
This study investigates the relationship between poverty and unemployment, Human Development Index (HDI), and Gross Regional Domestic Product (GDP) as major factors in looking at poverty rates. By using data on East Nusa Tenggara Province from 2017-2022, this study aims to determine the dominant factors that influence thehigh number of poor people in NTT Province. The results of the study can provide deep insights into the complex dynamics involving economic inequality, job resilience, and people's quality of life. With a better understanding of this correlation, it is hoped that policies can be designed that are more effective in addressing the challenges of poverty and improving overall well-being.